Relationship between Implementation and Performance of Integrated Information System with Service Efficiency in Improving Service Quality in Radiology Installation of Bogor City Regional General Hospital - Sugianty Syam; Roy Glenn Albert Massie; Jones Zenas Rante; Ratnawati Prayogi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Radiology services are a crucial component of the healthcare system that requires efficiency in its processes. Resource limitations and increasing demand for services underscore the importance of improving efficiency. To enhance service quality and operational efficiency, the implementation of an integrated information system has become a key focus for hospital management. Improving service quality and operational efficiency through the application of an integrated information system is also dependent on the reliability and performance of the system itself. This study aims to examine the relationship between the implementation and performance of an integrated information system with service efficiency in enhancing service quality in the radiology department of RSUD Kota Bogor. The research uses a quantitative approach with two independent variables: the implementation of the integrated information system and the reliability and quality of the integrated information system. The dependent variable is the quality of radiology services, and the intervening variable is radiology service efficiency. Data collection methods include observations, questionnaires, and documentation studies. The sample consists of 30 employees working in the radiology department of RSUD Kota Bogor and 30 patients receiving services in the radiology department. Data processing and presentation were conducted using path analysis with Structural Equation Modeling (SEM-PLS) using SmartPLS software. The results of the data analysis indicate that: (1) The implementation of the integrated information system does not have a significant relationship with radiology service efficiency; However, the reliability and performance of the system do have a strong relationship with radiology service efficiency. (2) The implementation and performance of the integrated information system do not have a significant relationship with service quality in the radiology department. (3) Radiology service efficiency has a significant relationship with service quality in the radiology department. (4) Radiology service efficiency, as a mediator, is not strong enough to enhance the relationship between the implementation and performance of the integrated information system and service quality in the radiology department. This study is expected to provide a comprehensive overview of the relationship between the implementation and performance of an integrated information system with service efficiency in enhancing service quality in the radiology department. The findings may serve as input for the management of RSUD Kota Bogor in optimizing the use of an integrated information system to improve radiology service efficiency, which is expected to impact the quality of services in the radiology department.